Formulation Antiseptics Artisan Soap From Extract Secang Wood (Caesalpinia sappan L.) And Kaffir Lime Leaves (Citrus hystrix DC.) - Nugroho, Priyanto Dwi; Latirah, Latirah; Irwandi, Dodi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2023)
Solid soap as a body skin cleanser can be used as a souvenir. Kaffir lime leaves and sappanwood are natural ingredients and contains good anti-bacterial compound. This paper aims to explain how to make solid soap with shape of watermelon using thick extracts of kaffir lime leaves and sappanwood with a concentration of 1%. Kaffir lime leaf and sappanwood extracts were each made by soaking 300 g of powder in 500 mL pro analysis ethanol solvent for 48 hours and thickening using a rotary evaporator at a temperature of approximately 50 °C. The soap is made using the cold method (cold process). The research results showed that the soap had a fresh smell, solid shape, soft texture and color resembling the shape of a watermelon. Has a pH of 9.8 ± 0.4 and free fatty acids of 1.39 ± 0.2, according SNI Soap. Artisan soap is also antiseptic and able to inhibit Escherichia coli and Staphylococcus aureus bacteria.